Review Of Maqasid Syariah Aspects Of Productive Waqf Management - Albab (Universitas Muhammadiyah Lampung), Ulil (Mu'amalatuna: Jurnal Ekonomi Syariah, 2024)
This research discusses the compatibility between maqasid sharia aspects and productive waqf management. The main objective of this research is to find out whether Waqf management practices have contributed to the dharuriyah needs of the community or not. In this case, waqf management is expected to have a beneficial function for religion and society where the distribution of property and its proceeds can be used for the welfare of society. The methodological approach used in this research is a phenomenological qualitative approach where phenomena related to maqasid sharia and productive waqf management are studied and discussed in depth. The data collection methods used in this research are observation, interviews, document analysis, and focus group discussions. The findings of this study show that productive waqf management is currently developed based on three pillars, namely education, business, and health. These pillars are developed to strengthen the institution in developing its assets, both material and non-material assets. Therefore, based on the management practices mentioned above, productive waqf management is considered to be in accordance with the Maqasid Syariah principle. The purpose of Maqasid Sharia is to create prosperity and welfare for the endowers. As an implication of this research, the management and development of waqf assets must be subject to supervision by a sharia supervisory body. The purpose of waqf management is for the welfare of society, and the purpose of maqasid sharia is for the benefit of society. Therefore, in waqf management, it is hoped that through the proceeds of waqf, the community can be helped and benefit and become more prosperous.